Dual blockade of VEGFR1 and VEGFR2 by a novel peptide abrogates VEGF-driven angiogenesis, tumor growth, and metastasis through PI3K/AKT and MAPK/ERK1/2 pathway - Sadremomtaz, Afsaneh; Mansouri, Kamran; Alemzadeh, Golnaz; Safa, Majid; Rastaghi, Ahmadreza Esmaeili; Asghari, S. Mohsen (Biochimica et biophysica acta. General subjects, 2018)
Neutralization of vascular endothelial growth factor receptor 1 (VEGFR1) and/or VEGFR2 is a widely used means of inhibiting tumor angiogenesis. Based on the complex X-ray structures of VEGFA/VEGFR1, VEGFA/VEGFR2, and VEGFB/VEGFR1, a peptide (referred to as VGB) was designed to simultaneously bind to VEGFR1 and VEGFR2, and binding, antiangiogenic and antitumor properties of the peptide was investigated in vitro. VGB bound to both VEGFR1 and VEGFR2 in human umbilical vein endothelial cells (HUVECs) and 4 T1 mammary carcinoma tumor (MCT) cells, and inhibited the proliferation of HUVE, 4 T1 MCT, and U87 glioblastoma cells. Through abrogation of AKT and ERK1/2 phosphorylation, VEGFA-stimulated proliferation, migration, and two- and three-dimensional tube formation in HUVECs were inhibited more potently by VGB than by bevacizumab. In a murine 4 T1 MCT model, VGB strongly inhibited tumor growth without causing weight loss, accompanied by inhibition of AKT and ERK1/2 phosphorylation, a significant decrease in tumor cell proliferation (Ki-67 expression), angiogenesis (CD31 and CD34 expression), an increase in apoptosis index (increased TUNEL staining and p53 expression and decreased Bcl-2 expression), and the suppression of systematic spreading of the tumor (reduced NF-κB and MMP-9 and increased E-cadherin expression). The dual specificity of VGB for VEGFR1 and VEGFR2, through which the PI3K/AKT and MAPK/ERK1/2 signaling pathways can be abrogated and, subsequently, angiogenesis, tumor growth, and metastasis are inhibited. This study demonstrated that simultaneous blockade of VEGFR1 and VEGFR2 downstream cascades is an effective means for treatment of various angiogenic disorders, especially cancer. •A novel peptide, referred to as VGB, was designed that simultaneously binds to VEGFR1 and VEGFR2.•VGB potently inhibited proliferation, migration, and tube formation of endothelial cells.•4T1 mammary carcinoma tumor growth and metastasis was inhibited by VGB.•VGB abrogated PI3K/AKT and MAPK/ERK1/2 signaling pathways in endothelial cells and tumor tissues.•In tumors, VGB led to the inhibition of angiogenesis and proliferation, and promoted apoptosis.